2003
DOI: 10.3758/bf03202549
|View full text |Cite
|
Sign up to set email alerts
|

Animated diagrams in teaching statistics

Abstract: In this study, we investigated whether computer-animated graphics are more effective than static graphics in teaching statistics. Four statistical concepts were presented and explained to students in class. The presentations included graphics either in static or in animated form. The concepts explained were the multiplication of two matrices, the covariance of two random variables, the method of least squares in linear regression, alpha error, beta error, and strength of effect. A comprehension test was immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Based on this understanding, they can tell a good story about ½÷¼. This finding is consistent with Wender and Muehlboeck (2003), who found that animated demonstration helped students learn mathematics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on this understanding, they can tell a good story about ½÷¼. This finding is consistent with Wender and Muehlboeck (2003), who found that animated demonstration helped students learn mathematics.…”
Section: Discussionsupporting
confidence: 85%
“…Next, the dynamic, animated, and interactive web‐based resources were shown to students. Interactive web‐based instruction was developed as research suggests that animated demonstration may be more efficiently processed by learners than without animated demonstration (Wender & Muehlboeck, 2003). Therefore, students in the web‐based instruction had more tasks, making use of dynamic animated representations on computers.…”
Section: Methodsmentioning
confidence: 99%
“…By virtue of our visual system, we may be able to quickly understand a complicated method or result, or at least a simplified case. Wender and Muehlboeck (2003) showed the advantages of animations in teaching statistical topics like least squares and type I & II errors. Velleman and Moore (1996) discussed a set of animation ideas that can be effective for a student to learn concepts actively.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers believe that animations have a greater flexibility in depicting physical and temporal changes than static pictures (Bétrancourt & Tversky, 2000;Castro-Alonso, Ayres, & Paas, 2014a, p. 552;Lowe, 2003), and are often assumed to be superior to static pictures (Chandler, 2009). There is supporting evidence showing that animations are more effective than static pictures when teaching statistics (e.g., Wender & Muehlboeck, 2003), physics (e.g., Rebetez, Bétrancourt, Sangin, & Dillenbourg, 2010;Rieber, 1990Rieber, , 1991b, geometry (e.g., Thompson & Riding, 1990), zoology (e.g., Pfeiffer, Scheiter, Kühl, & Gemballa, 2011), computer algorithm (e.g., Byrne, Catrambone, & Stasko, 1999), and motor-related tasks (e.g., Akinlofa, Holt, & Elyan, 2013;Ayres, Marcus, Chan, & Qian, 2009; Castro-Alonso, Ayres, & Paas, 2015a;Garland & Sánchez, 2013;Michas & Berry, 2000;A. Wong et al, 2009).…”
Section: Introductionmentioning
confidence: 92%